Severity assessment in rabbits after partial hepatectomy: Part II. (December 2016) - Drude, N; Pawlowsky, K; Tanaka, H; Fukushima, K; Kögel, B; Tolba, R H
Although the recognition of pain, distress and discomfort has already been described in 1985 by Morton and Griffiths there is still very little known about the establishment of score sheets especially, regarding post-surgical pain and severity assessment for laboratory animals such as rabbits. In this paper we describe the estimation of severity and recovery status of 36 female New Zealand White rabbits (NZW) in a standardized liver resection model using two different adhesive treatments and one control group. Welfare was assessed at 3–4 consecutive days after surgery using a scoring system which included the following criteria: body weight, general state, clinical results, spontaneous behavior and clinical examination. Values could range from 0 to 20 where increasing values indicated increasing severity with a predefined humane endpoint for a score ≥20 points. Documented score points were almost exclusively a result of body weight loss, whereas clinical signs and general health status had no influence on the overall sum of points scored. Behavioral variation was solely observed postoperatively, within the first 24 h, with an average score ≤1. In contrast to the classification of a laparotomy as a moderate procedure in the EU Directive 2010/63 (annex VIII) the assessment herein presented showed a mild burden in all groups according to the scoring system used. The partial hepatectomy itself, as well as the adhesive treatment using either synthetic glue VIVO-107 or fibrin glue, were well tolerated.